Forecasting of the Time-dependent Fluxes of Antiprotons in the AMS-02 Era - Zhu, Cheng-Rui; Duan, Kai-Kai (The Astrophysical journal, 2025)
The spectra of Galactic cosmic rays (GCRs) contain crucial information about their origin and propagation through the interstellar medium. When GCRs reach Earth, they are significantly influenced by the solar wind and the heliospheric magnetic field, a phenomenon known as solar modulation. This effect introduces time-dependent variations in GCR fluxes. The AMS-02 experiment has released time-dependent flux data for protons, electrons, and positrons, revealing clear correlations with solar modulation. Studies suggest that cosmic rays with the same charge, such as protons and helium nuclei, exhibit similar or the same solar modulation parameters. In this work, we derive the local interstellar spectrum (LIS) for protons and positrons under the assumption of a common solar modulation potential, using data from Voyager 1 and a 7 yr average from AMS-02. Similarly, the LIS for antiprotons and electrons is derived by assuming they are governed by a separate solar modulation potential. We demonstrate that the time-dependent fluxes of positrons and protons can be accurately modeled using the same set of solar modulation parameters within a modified force-field approximation framework. Based on this, we predict the time-dependent fluxes of antiprotons using the corresponding electron flux data.